AN SFL ANALYSIS OF PROCESS AND MOOD TYPES IN ENGLISH JOURNAL ARTICLES ON FINANCE - Thi Thanh Hoa, Nguyen (VNU Journal of Foreign Studies; Vol 38 No 3, 2022)
Journal articles written by Vietnamese authors have received strong criticism against their weaknesses, one of which is their failure to comply with international requirements (State Council for Professorship, 2016-2017). What are common international requirements for journal articles is therefore an essential subject of research, and the analysis in this paper from Systemic Functional Linguistics perspective is one of such attempts. A total of 50 articles randomly selected from 10 Scopus-indexed journals on finance and finance-related fields published in English are analyzed in order to answer the following specific questions: (1) what types of process and mood are used in English journal articles on finance?, and (2) what are they used for? This critical knowledge of processes and moods and their functions in English journal articles on finance will help Vietnamese authors to improve the quality of their articles for international publication.